A repetitive protein essential for the flagellum attachment zone filament structure and function in Trypanosoma brucei. - Vaughan, S; Kohl, L; Ngai, I; Wheeler, R; Gull, K (2008)
The flagellum is attached along the length of the cell body in the protozoan parasite Trypanosoma brucei and is a defining morphological feature of this parasite. The flagellum attachment zone (FAZ) is a complex structure and has been characterised morphologically as comprising a FAZ filament structure and the specialised microtubule quartet (MtQ) plus the specialised areas of flagellum: plasma membrane attachment. Unfortunately, we have no information as to the molecular identity of the FAZ filament components. Here, by screening an expression library with the monoclonal antibody L3B2 which identifies the FAZ filament we identify a novel repeat containing protein FAZ1. It is kinetoplastid-specific and provides the first molecular component of the FAZ filament. Knockdown of FAZ1 by RNA interference (RNAi) results in the assembly of a compromised FAZ and defects in flagellum attachment and cytokinesis in procyclic trypanosomes. The complexity of FAZ structure and assembly is revealed by the use of other monoclonal antibody markers illustrating that FAZ1 is only one protein of a complex structure. The cytokinesis defects provide further evidence for the role of an attached flagellum in cellular morphogenesis in these trypanosomes.